2005
DOI: 10.1016/j.cell.2005.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Surface Calreticulin Initiates Clearance of Viable or Apoptotic Cells through trans-Activation of LRP on the Phagocyte

Abstract: Apoptotic-cell removal is critical for development, tissue homeostasis, and resolution of inflammation. Although many candidate systems exist, only phosphatidylserine has been identified as a general recognition ligand on apoptotic cells. We demonstrate here that calreticulin acts as a second general recognition ligand by binding and activating LDL-receptor-related protein (LRP) on the engulfing cell. Since surface calreticulin is also found on viable cells, a mechanism preventing inadvertent uptake was sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
1,275
4
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,262 publications
(1,333 citation statements)
references
References 42 publications
39
1,275
4
15
Order By: Relevance
“…Recently, it has been suggested that calreticulin may function as a second general recognition ligand, via binding and activating LRP or CD91 on engulfing cells. 14 Arur et al 37 have suggested that annexin I may function in the facilitation of or enhancement of the recognition of PS by the receptor. Whether calreticulin or annexin I is related to stabilin-2-mediated phagocytosis is currently unclear, and will require further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested that calreticulin may function as a second general recognition ligand, via binding and activating LRP or CD91 on engulfing cells. 14 Arur et al 37 have suggested that annexin I may function in the facilitation of or enhancement of the recognition of PS by the receptor. Whether calreticulin or annexin I is related to stabilin-2-mediated phagocytosis is currently unclear, and will require further study.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, several scavenger receptors have been theorized to mediate the binding and uptake of aged/apoptotic cells, including LOX-1, 10 CD36, 11 Drosophila Croquemort, 12 and low-density lipoprotein (LDL)-receptor-related protein (LRP1, also referred to as CD91). 13,14 These receptors may function in parallel or redundant phagocytic systems, as the blocking of any receptor impairs apoptotic cell engulfment only partially. 15 Although these receptors have been implicated in the engulfment of aged/apoptotic cells, no evidence has yet been presented to show that any of these receptors can directly recognize PS.…”
mentioning
confidence: 99%
“…31,32 Recently, calreticulin appearing on the surface of apoptotic cells was found to initiate their clearance acting together with PS for achieving optimal phagocytic clearance of cells. 33 Changing carbohydrate composition of glycoproteins 34 and exposure of DNA on dying cells 35 have been proposed as alternative mechanisms to PS for recognition of dead cells. Further studies are required to determine whether these alternative 'eat me' signals or others are exposed on the surface of cells dying through autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…8 Other less-characterized recognition signals as well as the respective receptors they engage on phagocytes are depicted in Figure 2. [9][10][11] Factors such as the cell type undergoing death, the pathological or physiological stimulus, or the duration of this fatal process can affect the landscape of eat-me signals exposed.…”
Section: Steps Involved In Clearancementioning
confidence: 99%